Shilpa Gupta - Weibel, Peter; Adajania, Nancy; Mirza, Quddus; Jhaveri, Shanay (Munich: Prestel, 2009)
Poised at the intersection of art and technology, the sacred and the secular, Shilpa Gupta's work occupies many contexts: post-feminist art, technology-enabled art and transcultural art. This book discusses Gupta's work from the perspectives of new media, religious politics, the critique of the nation state and global violence.
The media of absence / Peter Weibel -- To see again and again / Shanay Jhaveri -- The unusual suspect / Quddus Mirza -- Darkness is what light will never be : Shilpa Gupta's experiments with truth / Nancy Adajania.
boek
Keywords: Gupta, Shilpa; India